MICRO, SMALL, AND MEDIUM ENTERPRISES (MSMEs) EMPOWERMENT THROUGH QUADRUPLE HELIX APPROACH IN BATU CITY - Lely Indah Mindarti; Ajie Hanif Muzaqi (NATAPRAJA, 2020)
The research  purpose is to describe implementing of MSMEs empowerment in Batu using perspective of Quadruple helix model . This research using descriptive qualitative approach. Government of Batu through Department of Micro Enterprise Cooperatives and Trade of Batu implements MSMEs empowerment by relying on 4 main factors of empowerment: financial capital access, human resource, partnership, and market strengthening.  This government also established Integrated Business Service Centre (IBSC) as one of the commitments in empowering MSMEs and also making Batu as MSMEs centre. The result of analysis using the concept of Quadruple helix model  found that MSMEs empowerment in Batu involves collaboration of different sectors: the government of Batu, private/business institutions, academics, and civil society through communities, groups, and non-governmental organizations. Thus, the government of Batu plays dominant roles in the interaction synergies of different sectors and being responsible in equitable economic development. Private institutions play roles as production developer, academics play roles as knowledge and skill development transferor and civil society plays roles as creative economic agents and product users